2016
DOI: 10.1080/15476286.2016.1218588
|View full text |Cite
|
Sign up to set email alerts
|

Expression dynamics, relationships, and transcriptional regulations of diverse transcripts in mouse spermatogenic cells

Abstract: Among all tissues of the metazoa, the transcritpome of testis displays the highest diversity and specificity. However, its composition and dynamics during spermatogenesis have not been fully understood. Here, we have identified 20,639 message RNAs (mRNAs), 7,168 long non-coding RNAs (lncRNAs) and 15,101 circular RNAs (circRNAs) in mouse spermatogenic cells, and found many of them were specifically expressed in testes. lncRNAs are significantly more testis-specific than mRNAs. At all stages, mRNAs are generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 58 publications
3
78
1
Order By: Relevance
“…As for SSCs, Dong, Li, Qing, Huang, and Li () revealed a total of 15,996 circRNAs were identified in human testis using high‐throughput sequencing and 14,033 (87.7%) circRNAs were mapped to 5,928 host genes, involving several genes required for SSC self‐renewal, such as STK31, suggesting the potential role of circRNAs in SSC self‐renewal. In the study performed by Lin et al (), 5,573 circRNAs were identified to be expressed in SSC and the average level of circRNAs exhibited dynamic changes during male germ cell development, indicating these circRNAs probably involved in SSC self‐renewal and differentiation. A recent study, to probe the functions of circRNAs in GSCs including SSCs and female GSCs (FGSCs), X. Li, Ao, and Wu () explored the expression profiles of circRNAs in mouse SSCs and FGSCs by high‐throughput sequencing and a total of 18,822 circRNAs derived from 5,334 hosting genes were identified in the mouse GSCs.…”
Section: Ncrna In Sscs Self‐renewalmentioning
confidence: 99%
“…As for SSCs, Dong, Li, Qing, Huang, and Li () revealed a total of 15,996 circRNAs were identified in human testis using high‐throughput sequencing and 14,033 (87.7%) circRNAs were mapped to 5,928 host genes, involving several genes required for SSC self‐renewal, such as STK31, suggesting the potential role of circRNAs in SSC self‐renewal. In the study performed by Lin et al (), 5,573 circRNAs were identified to be expressed in SSC and the average level of circRNAs exhibited dynamic changes during male germ cell development, indicating these circRNAs probably involved in SSC self‐renewal and differentiation. A recent study, to probe the functions of circRNAs in GSCs including SSCs and female GSCs (FGSCs), X. Li, Ao, and Wu () explored the expression profiles of circRNAs in mouse SSCs and FGSCs by high‐throughput sequencing and a total of 18,822 circRNAs derived from 5,334 hosting genes were identified in the mouse GSCs.…”
Section: Ncrna In Sscs Self‐renewalmentioning
confidence: 99%
“…To test this hypothesis, we further examined the stage-specific circRNA expression profiles of different spermatogenic cells (spermatogonia, spermatocyte, and spermatid) from a published dataset for mice (Lin et al, 2016) and cross-analyzed the spermatogenic stage-specific gene categories with the age-specific circRNA signatures observed in rats. Interestingly, we found that the overall fraction of circular transcripts increased monotonically with the spermatogenesis stage in mice (spermatogonia, spermatocytes, and spermatids, sequentially) (Spearman's rank correlation test: ρ = 0.772 and P = 2.5×10 -2 ; Figure 6C).…”
Section: Age-dependent Circrna Expression In Testesmentioning
confidence: 99%
“…To further investigate age-sensitive testicular circRNA expression, we also obtained raw RNA-seq data for mouse spermatogenic cells from the NCBI GEO database (Barrett et al, 2013) under accession code GSE75826. This dataset contains rRNA-depleted RNA-seq data from three different types of spermatogenic cells: spermatogonia, spermatocytes, and spermatids (Lin et al, 2016).…”
Section: Raw Rna-seq Datamentioning
confidence: 99%
“…In this context, it is interesting to underline that genomewide waves of transcription occur during the development and differentiation of male germ cells. These genome-wide waves of transcription are the consequences of the genome-wide epigenetic "reprogramming" occurring during male germ cell development and differentiation [159][160][161][162]. As a consequence, male germ cells produce the most complex set of coding and noncoding transcripts and alternative splicing variants [159][160][161][162].…”
Section: Do Co-translational Physical Constraints Drive Dna Sequence mentioning
confidence: 99%
“…These genome-wide waves of transcription are the consequences of the genome-wide epigenetic "reprogramming" occurring during male germ cell development and differentiation [159][160][161][162]. As a consequence, male germ cells produce the most complex set of coding and noncoding transcripts and alternative splicing variants [159][160][161][162]. Therefore, male germ cells may experience extensive transcription-mediated genomic instability that could explain the large-scale apoptosis of immature sperm cells [4,163,164].…”
Section: Do Co-translational Physical Constraints Drive Dna Sequence mentioning
confidence: 99%